Analysis of The Effect Of Experiential Marketing With The Concept Of "Better" Model and Emotional Branding on Consumer Loyalty - Anik, Minhaju Dikri; Wahib Muhaimin, Abdul; Shinta HW, Agustina (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to describe experiential marketing factors with the concept of "BETTER" model and emotional branding on consumer loyalty, and analyze the influence of the "BETTER" model and Emotional Branding Factors on customer satisfaction and loyalty. The research location is at Bale Luwe Restaurant in Malang City. The sampling method in this study was non-probability sampling with a purposive sampling approach. The number of respondents was 100 respondents. Furthermore, the analysis method in the study used descriptive analysis and Structural Equation Modeling (SEM) analysis with the Warp Partial Least Square (WarpPLS) approach. Primary data was obtained through interviews and filling out online questionnaires, as well as field observations. Meanwhile, secondary data were obtained through literature studies from various related sources. The results of the Structural Equation Modeling (SEM) analysis show that Brand personality with sense indicators, Emotional Connection with feel indicators, Target audience with Think indicators, Exponential Element with act indicators, Two-way interaction with relate indicators and emotional branding variables all have a positive and significant effect on consumer loyalty.